2015
DOI: 10.5194/bgd-12-15495-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No-tillage lessens soil CO<sub>2</sub> emissions the most under arid and sandy soil conditions: results from a meta-analysis

Abstract: Abstract. The management of agroecosystems plays a crucial role in the global carbon cycle with soil tillage leading to known organic carbon redistributions within soils and changes in soil CO2 emissions. Yet, discrepancies exist on the impact of tillage on soil CO2 emissions and on the main soil and environmental controls. A meta-analysis was conducted using 46 peer-reviewed publications totaling 174 paired observations comparing CO2 emissions over entire seasons or years from tilled and untilled soils across… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 111 publications
5
4
0
Order By: Relevance
“…NT) should be recommended in semi-arid areas. Supporting our findings, the recent meta-analysis of Abdalla et al (2015) pointed out that the abatement of C02-eq emissions through NT adoption is significantly higher in arid climates with low SOC content, as opposed to CT. Nitrous oxide (N2O) emissions have shown to carry less weight in GWP estimates than in previous studies (Mosier et al, 2006;Adviento-Borbe et al, 2007), but uncertainties associated with SOC accumulation and its calculation (Guardia et al, 2016) and the large climatic variability in rainfed semi-arid cropping areas, suggest that strategies that mitigate C0 2 -eq from other GWP components (N 2 0 losses and inputs, e.g. by adjusting N rates) must be also considered.…”
Section: Global Warming Potentialsupporting
confidence: 76%
See 1 more Smart Citation
“…NT) should be recommended in semi-arid areas. Supporting our findings, the recent meta-analysis of Abdalla et al (2015) pointed out that the abatement of C02-eq emissions through NT adoption is significantly higher in arid climates with low SOC content, as opposed to CT. Nitrous oxide (N2O) emissions have shown to carry less weight in GWP estimates than in previous studies (Mosier et al, 2006;Adviento-Borbe et al, 2007), but uncertainties associated with SOC accumulation and its calculation (Guardia et al, 2016) and the large climatic variability in rainfed semi-arid cropping areas, suggest that strategies that mitigate C0 2 -eq from other GWP components (N 2 0 losses and inputs, e.g. by adjusting N rates) must be also considered.…”
Section: Global Warming Potentialsupporting
confidence: 76%
“…As reported by previous studies (e.g. Aguilera et al, 2013aAguilera et al, , 2015Plaza-Bonilla et al, 2015;Abdalla et al, 2015), NT significantly increased the SOC content compared with CT (Table 3). This occurred despite the higher SOC content in the 15-30 cm layer in CT (as opposed to NT/MT), as suggested by Baker et al (2007).…”
Section: Global Warming Potentialsupporting
confidence: 74%
“…This finding was in agreement with Guardia et al (2016a) and Aguilera et al (2015). Results from a recent meta-analysis (Abdalla et al, 2015) concluded that NT system significantly reduced CO 2 -eq emissions and increased soil C stock particularly under arid and sandy soil conditions with low SOC content, supporting our findings. In spite of low weight of N 2 O emissions in net-GWP and the uncertainties associated to the calculation of C sequestration (Guardia et al 2016a), long-term NT system can be considered as a good strategy to mitigate CO 2 -eq emissions and increase the generally low SOC content of Mediterranean soils compared to MT and CT systems in rainfed semiarid agro-ecosystems.…”
Section: Effect Of Conservation Tillage On Ghg Emissions Under Meditesupporting
confidence: 92%
“…Those soil types have, on average, a clay content of about 30 and 45%, respectively, which may help to slowdown SOC decomposition compared to coarser soils [58,59]. This is related to the fact that clay particles can help to stabilise decomposing litter by mineral associated bonds [1,2] and the aggregation is stronger, also promoting physical inaccessibility of SOC to the microbial community [3].…”
Section: Reasons For Heterogeneitymentioning
confidence: 99%